Human action recognition: a construction of codebook by discriminative features selection approach. (2018) - Siddiqui, Samra; Khan, Muhammad Attique; Bashir, Khalid; Sharif, Muhammad; Azam, Faisal; Javed, Muhammad Younus
Human activity recognition (HAR) has significance in the domain of pattern recognition. HAR handles the complexity of human physical changes and heterogeneous formats of same human actions performed under dissimilar subjects. This research contributes a unique method focusing on the changes in human movement. The purpose is to identify and categorise human actions from video sequences. The interest points (IPs) are extracted from the subject video and motion history images (MHIs) are constructed and analysed after image segmentation. Discriminative features (DFs) are selected and the visual vocabulary is learned from the extracted DF (EDF). The EDF are then quantised by using visual vocabulary and images are represented based upon frequencies of visual words (VW). VW are formed from the EDF and then, a histogram of VW is developed based on the feature vectors extracted from MHI. These feature vectors are used for training support vector machine (SVM) for the classification of actions into various categories. Benchmark datasets like KTH, Weizmann and HMDB51 are used for evaluation and comparison with existing action recognition approaches depicts the better performance of adopted strategy.